Deep metagenomic characterization of gut microbial community and function in preeclampsia - Lv, Li-Juan; Li, Sheng-Hui; Wen, Ji-Ying; Wang, Guang-Yang; Li, Hui; He, Tian-Wen; Lv, Qing-Bo; Xiao, Man-Chun; Duan, Hong-Li; Chen, Min-Chai; Yi, Zhou-Ting; Yan, Qiu-Long; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Preeclampsia (PE) is a pregnancy complication characterized by severe hypertension and multiple organ damage. Gut microbiota has been linked to PE by previous amplicon sequencing studies. To resolve the PE gut microbiota in a higher taxonomy resolution, we performed shotgun metagenomic sequencing on the fecal samples from 40 early-onset PE and 37 healthy pregnant women. We recovered 1,750 metagenome-assembled genomes (representing 406 species) from the metagenomic dataset and profiled their abundances. We found that PE gut microbiota had enriched in some species belonging to Blautia, Pauljensenia, Ruminococcus, and Collinsella and microbial functions such as the bacitracin/lantibiotics transport system, maltooligosaccharide transport system, multidrug efflux pump, and rhamnose transport system. Conversely, the gut microbiome of healthy pregnant women was enriched in species of Bacteroides and Phocaeicola and microbial functions including the porphyrin and chlorophyll metabolism, pyridoxal-P biosynthesis, riboflavin metabolism, and folate biosynthesis pathway. PE diagnostic potential of gut microbial biomarkers was developed using both species and function profile data. These results will help to explore the relationships between gut bacteria and PE and provide new insights into PE early warning.